(untitled) (Journal of Laboratory Animal Science, 2022)
Animals are used in research to study some of cell structures and physiological and pathological processes. The results obtained are correlated to the human body. The acute toxicity study of the fractions and isolated pytoconstituents of Hemidesmus indicus was performed as per OECD guidelines 425 at a dose of 4000mg/kg. The present study was carried out to evaluate the anti-inflammatory activity of ethanolic extract of Hemidesmus indicus leaves in experimental animals using in vivo model like carrageenan induced rat paw oedema method and invitro method like Inhibition of albumin denaturation. In this method, the rats were tested with oral administration of ethanolic extract of Hemidesmus indicus leaves as a test drug.